EFFECTS OF TEXTILE WASTEWATER PRE-TREATMENT ON LIGNOCELLULOSIC BIOMASS FOR SOLID-STATE ANAEROBIC DIGESTION - Abubakar, M. S.; Yazid, A. B.; Sabo, A. A.; Ibrahim, A.; Aliyu, A. U.; Saleh, M. (FUDMA JOURNAL OF SCIENCES, 2023)
Researchers are looking into sustainable and inexpensive energy sources due to the constant rise in the price of fossil fuels, greenhouse gas emissions, and dependence on non-renewable energy sources. In this study, wastewater from the textile industry is co-digested with lignocellulosic biomass (wheat straw) to produce biogas. During 21 days, five anaerobic digesters were run at room temperature (28 to 30 0C). Wheat straw inoculated with cow manure was put into wheat straw operating in five digesters at five different ratios of wastewater to distilled water. It has been discovered that the slurry digested with mere wastewater (not diluted with distilled water) has the lowest production, while the slurry digested with wheat straw and cow dung has the highest production.
Keywords: Textile wastewater; lignocellulosic biomass; Solid-state anaerobic digestion